2019
DOI: 10.3390/ijerph16183432
|View full text |Cite
|
Sign up to set email alerts
|

Role of Parenting Styles in Adolescent Substance Use Cessation: Results from a Brazilian Prospective Study

Abstract: Background: This study aims to identify the association between parenting styles and behavioral changes among adolescents regarding the consumption of alcohol, tobacco, cannabis, cocaine/crack. Methods: A group of ninety-nine adolescents (39 girls and 60 boys), aged 14 to 19 years (17.05 ± 1.51), who called in to a call center that provides counseling to substance users, was followed-up for 30 days. Data collection occurred between March 2009 and October 2015. The adolescents answered questions regarding paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…This approach to health is more critical for children in critical developmental stages that need full support from their parents [53,54]. In line with our findings, our study expresses the importance of the role of parents [54][55][56]. Depending on their parenting style, children can have differing outcomes in mental health when they are growing up [57,58].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This approach to health is more critical for children in critical developmental stages that need full support from their parents [53,54]. In line with our findings, our study expresses the importance of the role of parents [54][55][56]. Depending on their parenting style, children can have differing outcomes in mental health when they are growing up [57,58].…”
Section: Discussionsupporting
confidence: 86%
“…The WHO states that well-being can be achieved when mental and physical health are balanced [52]. This approach to health is more critical for children in critical developmental stages that need full support from their parents [53,54]. In line with our findings, our study expresses the importance of the role of parents [54][55][56].…”
Section: Discussionsupporting
confidence: 86%
“…This style of parenting, consisting of “hyper-involvement” in children’s activities, has been associated with poor social skills and self-efficacy [ 125 ]. This particular finding is interesting, for recent studies show that indulgent/permissive parenting seems to result in more positive outcomes in youngsters with higher self-esteem and good educational performance [ 11 ], shedding more light on the degree of responsiveness required and also the developmental timeframe for such variation. The social fabric has witnessed changes of the highest magnitude with the drastic measures imposed by multiple countries since the coronavirus (Covid-19) outbreak in 2020 which may seem to favor permissive parenting style as reported by the positive effects on the behavioural traits in Japanese children [ 90 ].…”
Section: Research Gap and Future Directionmentioning
confidence: 91%
“…Neglectful parents fail to set limits and do not provide their children with adequate warmth, rendering them more vulnerable to substance abuse [ 10 ]. A Brazilian prospective study involving 99 adolescents reported 30% and 28% respondents exposed to authoritative and neglectful parenting respectively; with adolescents from the latter having more trouble abstaining from substance abuse [ 11 ]. These findings align with reports from Martínez-Loredo et al [ 80 ] demonstrating a strong link between neglectful parenting and adolescent alcohol abuse with an odds ratio (OR): 2.14; 95% confidence interval (CI): 1.18–3.86 (p = 0.012).…”
Section: Consequential Effects Of Ineffective Parentingmentioning
confidence: 99%
“…In recognition of this empirical support, the Residential Care Consortium released a white paper advocating that residential programs improve parent engagement, particularly prior to and following discharge to the community when disruptions in care are common [ 13 ]. Further research has suggested that adolescent substance use interventions targeting parental monitoring and communication, two key parenting processes that are protective against adolescent substance use [ 14 , 15 ], are associated with better adolescent outcomes than interventions targeting parent education only [ 16 - 18 ].…”
Section: Introductionmentioning
confidence: 99%